Interaction between arbuscular mycorrhizal fungi and dark septate endophytes in the root systems of Populus euphratica and Haloxylon ammodendron under different drought conditions in Xinjiang, China - Wang, Huimei; Wang, Hengfang; Wei, Shengtao; Sun, Li; Cheng, Linlin (Frontiers in Plant Science, 2025)
Background and AimsArbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE) are known to enhance the tolerance of host plants to biotic and abiotic stresses, but the mechanism of their interaction under natural conditions has not been extensively studied.MethodsWe analyzed the endophytic fungal diversity and colonization characteristics in the typical desert plants Populus euphratica and Haloxylon ammodendron and the relationship between them and environmental factors.ResultsExcept for DSE in the roots of H. ammodendron, the colonization rates of AMF and DSE were significantly positively correlated with drought severity. The abundance of AMF and DSE under medium and mild drought conditions was greater than that under severe drought conditions. The root colonization rate and abundance of AMF were lower than those of DSE under the same drought conditions. The species diversity and abundance of AMF and DSE in P. euphratica were greater than those in H. ammodendron. AMF were more susceptible to soil factors such as soil water content, soil nitrogen and phosphorus content, and urease, whereas DSE were more affected by pH.ConclusionDrought stress has different effects on AMF and DSE in the roots of P. euphratica and H. ammodendron. DSE have a greater advantage in extremely arid environments. This study demonstrates the interaction between AMF and DSE with the host plants P. euphratica and H. ammodendron as well as their effects on the adaptation of host plants to the desert environment, which can provide a basis for strengthening desert vegetation management.